2017
DOI: 10.1186/s12891-017-1667-1
|View full text |Cite
|
Sign up to set email alerts
|

Glenohumeral and scapulothoracic strength impairments exists in patients with subacromial impingement, but these are not reflected in the shoulder pain and disability index

Abstract: BackgroundPain and loss of function are cardinal symptoms associated with Subacromial impingement syndrome (SIS), while the presence and magnitude of deficits in strength and range of motion (ROM) are largely undescribed in non-athletic patients with SIS. Moreover, the relevance of impairments in strength and ROM to patient-reported shoulder function is not well described, even though testing of strength is recommended in clinical guidelines.The purpose of this study was, first, to investigate impairments in g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
43
1
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 34 publications
0
43
1
2
Order By: Relevance
“…Resistance training, aimed at strengthening the rotator cuff muscles and scapula stabilising muscles, is an important component of most novel exercise interventions for long-lasting SIS [ 9 , 12 , 13 ]. This seems relevant as patients with SIS have significant force impairments in both the glenohumeral and the scapulothoracic joint [ 4 , 14 , 15 ]. However, these force impairments are most pronounced in the glenohumeral joint, with a 33% deficit in external rotation force and a 29% deficit in abduction force compared to only 8% and 18% force deficit in protraction and retraction of the scapula, respectively [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Resistance training, aimed at strengthening the rotator cuff muscles and scapula stabilising muscles, is an important component of most novel exercise interventions for long-lasting SIS [ 9 , 12 , 13 ]. This seems relevant as patients with SIS have significant force impairments in both the glenohumeral and the scapulothoracic joint [ 4 , 14 , 15 ]. However, these force impairments are most pronounced in the glenohumeral joint, with a 33% deficit in external rotation force and a 29% deficit in abduction force compared to only 8% and 18% force deficit in protraction and retraction of the scapula, respectively [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…This seems relevant as patients with SIS have significant force impairments in both the glenohumeral and the scapulothoracic joint [ 4 , 14 , 15 ]. However, these force impairments are most pronounced in the glenohumeral joint, with a 33% deficit in external rotation force and a 29% deficit in abduction force compared to only 8% and 18% force deficit in protraction and retraction of the scapula, respectively [ 15 ]. This suggests that specific training of the glenohumeral muscles is especially relevant.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The condition is characterized by shoulder pain and impaired patient-reported function ( Roach et al, 1991 ), but reduced strength and range of motion (ROM) has also been reported in patients with SIS ( Clausen et al, 2017 ; MacDermid et al, 2004 ). More specifically, abduction and external rotation strength, as well as abduction ROM, is only two-thirds of that in the unaffected shoulder ( Clausen et al, 2017 ) or healthy controls ( MacDermid et al, 2004 ), which is why a ∼50% increase is needed to reach normal strength and ROM levels. Based on this, it is suggested that patient-reported function, pain, strength and ROM should be considered core outcomes related to SIS ( Clausen et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…More specifically, abduction and external rotation strength, as well as abduction ROM, is only two-thirds of that in the unaffected shoulder ( Clausen et al, 2017 ) or healthy controls ( MacDermid et al, 2004 ), which is why a ∼50% increase is needed to reach normal strength and ROM levels. Based on this, it is suggested that patient-reported function, pain, strength and ROM should be considered core outcomes related to SIS ( Clausen et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%